Metabolic syndrome components after pediatric liver transplantation: prevalence and the impact of obesity and immunosuppression - Perito, Emily R. (Am J Transplant, 2016)
Metabolic syndrome is associated with long-term morbidity and mortality after adult liver transplant (LT). Whether pediatric LT recipients have a higher prevalence of metabolic syndrome remains controversial. In a cross-sectional study, we evaluated pediatric LT recipients aged 8–30 years using National Health and Nutrition Examination Survey (NHANES) protocols. LT recipients were matched by gender, race/ethnicity, and age with controls from NHANES. Pediatric LT recipients (n=83), after adjusting for overweight/obesity and glucocorticoid use, had increased prevalence of pre-hypertension and hypertension, impaired glucose tolerance (IGT; 2-hour glucose after oral glucose tolerance test ≥ 140mg/dL), and low HDL than matched NHANES controls (n=235) despite a lower prevalence of overweight/obesity. Among LT recipients, the adjusted odds of IGT doubled for every 7.5 years on calcineurin-inhibitors (CNIs, OR 2.10, 95% CI 1.06–4.17 per 7.5 years on CNIs, p=0.03). Among all subjects with IGT, LT recipients had a lower prevalence of overweight/obesity and less insulin resistance (HOMA-IR) than controls with IGT. Among normal weight subjects, LT recipients were significantly more likely than controls to have pre-hypertension/hypertension, IGT, low HDL, and metabolic syndrome. Pediatric LT recipients have unique metabolic syndrome profiles and risk factors, and will require tailored screening and management protocols.